2013
DOI: 10.3109/13880209.2013.824007
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive effect of the essential oil of tarragon (Artemisia dracunculus)

Abstract: This study reported the peripheral and central antinociceptive activity of the EOAD and rationalized the traditional use of the plant in the treatment of different painful conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Fructose is a greatly lipogenic carbohydrate that has thoughtful metabolic effects on the liver inducing de nova lipogenesis and glucogenesis [24]. Investigation established that demonstration of the extracts from two Artemisia species in mice could enhance insulin-responsive by altering the serine phosphorelation in insulin receptor and affecting on monocyte chemotactic protein-1 levels in visceral white Adipocyte Tissue [25]. High fructose utilization in modern diet is frequently connected with insulin resistance, and distressed glucose homeostasis [26].…”
Section: Discussionmentioning
confidence: 99%
“…Fructose is a greatly lipogenic carbohydrate that has thoughtful metabolic effects on the liver inducing de nova lipogenesis and glucogenesis [24]. Investigation established that demonstration of the extracts from two Artemisia species in mice could enhance insulin-responsive by altering the serine phosphorelation in insulin receptor and affecting on monocyte chemotactic protein-1 levels in visceral white Adipocyte Tissue [25]. High fructose utilization in modern diet is frequently connected with insulin resistance, and distressed glucose homeostasis [26].…”
Section: Discussionmentioning
confidence: 99%
“…The results in the present study indicated that Artemisia aqueous extract decreased the acute and chronic pain responses in FDWE group compared to FDW group. Maham et al in 2014 confirmed that essential oil of Artemisia dracunculus (EOAD) has peripheral and central antinociceptive effects in normal mice and it seems that a variety of mechanisms compared to opioid receptors are involved in the analgesic effect of EOAD [ 24 ]. Our results in this study showed that acute and chronic pain score in FDWE group is significantly lower than that of FDW group and it is confirmed by prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Maham et al [13] performed various experimental models on mice and rats to assess antinociception triggered by the EO of Artemisia dracunculus L. (Asteraceae) [13]. They also identified the LD 50 dose of the EO as 1250 mg/kg.…”
Section: Animal Studiesmentioning
confidence: 99%